ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA DE STEVIA (ENDULZANTE NATURAL) EN EL CANTÓN PALANDA Y SU COMERCIALIZACIÓN EN LA CIUDAD DE LOJA - Vacacela Chuquimarca, Alexander Vladimir (2018)
The objective of this investment project is to determine the feasibility for the creation of a company producing stevia (natural sweetener) in the Palanda canton and its commercialization in the city of Loja, based on studies: market, technical, administrative and financial. To achieve these objectives materials, method, techniques and instruments were used that allowed the achievement of the objectives. In the first instance, the research was based on literature review taken from some bibliographical sources. In the market study, the target market was determined and segmentation was carried out, obtaining a sample of 381 surveys, which generated customer information, potential, real and effective. For the technical study we moved to the sector where the Stevia will be produced and with the help of an Agronomist, the surface and the number of plants for the sowing were established and for the commercialization a suitable place was determined that fulfills all the requirements, physical as economic. Likewise, for the financial study the proformas of the commercial establishments were taken into account to elaborate the amount of investment and in this way a budget for the project during its useful life. And finally, the financial evaluation was developed based on the results obtained in the financial study in order to determine the feasibility of the project during its useful life. The results obtained are the following: an average consumption of 4713 gr per year per stevia family, the actual demand of the product is 41,348,801 gr and the effective demand of 20,729,335 gr per year. An offer of 286,000 grams of stevia and an unsatisfied demand of 20,435,756 grams is obtained. Regarding the technical study, it was determined that the installed capacity of 110,000 units per year, for the present study will be worked with a used capacity of 108,000 units per year and a market share of 54%. The macro location of the company is in region 7 of the equator, in the canton Palanda, province of Zamora Chinchipe. The micro location will be located in the Buena Vista farm, Fátima neighborhood in Palanda county In the engineering of the project, it is established that for every 8 hours of production, a total of 600 units of 100 gr per day of the product are obtained. As for the Legal and 5 Administrative Organization, it is defined under the concept of a single-member microcompany with limited liability, due to the favorable conditions that this type of organization presents. The financial study details the budgets required for the production and operation of the company with an investment amount of $ 68,293.98 for which a loan of $ 30,000.00 will be made in a BanEcuador financial institution with an interest rate of eleven%. The financial evaluation shows that the net present value is 30,693.66 which indicates that the project is convenient; the internal rate of return of the project is 21.74%, satisfactory; the cost benefit ratio shows that $ 0.34 will be earned from each dollar invested; the period in which the capital is recovered is 6 years 10 months; the sensitivity analysis indicates that the project will support an increase in costs of 11.14% and a decrease in revenues of 8.36% Giving as a conclusion that the project is feasible both in the production and for the investment since it will generate a great economic profitability, it is recommended that for the high consumption and reception of the sweetener in the market the publicity is made publicizing essentially the benefits and benefits that brings the sweetener not only to the health of the families but also in the economic part of them